Does the multilevel governance of state aid encourage broadband diffusion? Evidence from three European countries - Paolo Gerli; Julio Navio Marco; Jason Whalley (International Telecommunications Society (ITS), 2019)
EU broadband policy has been described as an example of multi-level governance (MLG) involving manifold actors across different sectors and levels of government. Whereas the extant literature has largely explored the interaction among public and private players and between national and supranational regulators in the context of the EU broadband markets, little attention has been paid to the MLG of state aid for broadband diffusion. This paper aims to fill such a research gap by employing multiple qualitative methods to explore how MLG has affected the implementation of public initiatives in support of broadband diffusion across Spain, Italy and the UK. The cross-country comparison reveals a trend towards the centralisation of public interventions, which created efficiencies in the management of state aid but raised tensions with local authorities. Therefore, the current MLG of state aid needs to be adjusted to balance the benefits of a greater coordination with the need urgency to ensure the effective and active participation of local stakeholders to the implementation of broadband projects.
Keywords: 330